Isolation and Molecular Characterization of Gelatinase-Producing Bacteria from Mangrove Sediment - Asep Awaludin Prihanto; Hidayatun Muyasyaroh; Abdul Aziz Jaziri; Nada Itorul Umam (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Protease is an important enzyme widely produced by microorganisms applied in food, health, and industry. Mangrove ecosystem, a rich microorganism habitat, accounted as a new resource for isolating the proteolytic bacteria. The purpose of this study was to identify protease-producing bacteria from mangrove ecosystems in the Tuban area, Indonesia. Three isolates that produced the gelatinase was successfully isolated from mangrove sediments. Bacterial isolates were then tested for extracellular gelatinase. The results showed that isolate T1 had high gelatinase activity. Two isolates (isolates T2 and T3) produced moderately gelatinase enzymes. Molecular identification revealed that isolate T1 is Enterobacter hormaechei.